Аналіз методів удосконалення процесу переробки органічних відходів тваринництва у метантенках - Скляр, Олександр Григорович; Скляр, Радміла Вікторівна; Болтянський, Борис Володимирович; Сиротюк, С. В.; Коробка, С. В.; Стукалець, І. Г.; Skliar, Oleksandr; Skliar, Radmila; Boltianskyi, Borys; Syrotyuk, S.; Korobka, S.; Stukalets, I. (Запоріжжя : 2024, 2024)
UA: В статті проаналізовано існуючі методи удосконалення процесу переробки органічних відходів тваринництва у метантенках. Розглянуті основні напрямки наукових досліджень інтенсифікації процесу анаеробної переробки гнойових стоків. А також доза завантаження метантенка та періодичність бродіння органічної сировини. Для проведення аналізу методів вдосконалення процесу анаеробної переробки гною та гнойових стоків у метантенках вони умовно були розділені на види: механічний, біохімічний, мікробіологічний, термічна та електромагнітна обробки. Наведені їх особливості роботи, переваги і недоліки при цьому. Аналіз методів удосконалення процесу переробки органічних відходів тваринництва у метантенках зведено у таблицю, де представлено суть удосконалення та очікуваний ефект. EN: The article analyzes the existing methods of improving the process of processing organic livestock waste in methane tanks. The active use of methanogenesis in the fermentation of organic waste is, according to modern ideas, one of the most promising ways to jointly solve environmental and energy problems at agricultural enterprises. The main directions of scientific research on the intensification of the process of anaerobic processing of sewage are considered. Improving the process of anaerobic fermentation of sewage is, first of all, reducing the fermentation cycle or the residence time of organic biomass in the methane tank. The loading dose of the methane tank and the frequency of fermentation of organic raw materials were analyzed. To analyze the methods of improving the process of anaerobic processing of manure and manure effluents in methane tanks, they were conditionally divided into types: mechanical, biochemical, microbiological, thermal and electromagnetic processing. One of the ways to improve the process of anaerobic processing of manure is the use of an anaerobic biofilter system to extend the life of methane-producing microorganisms in the working chamber of the methane tank. To maintain the required temperature regime in the fermentation chamber of the methane tank, there are two options: preliminary heating of the initial mass before loading, where the heat exchange devices are located outside the fermentation chamber of the methane tank, and heating of the fermentation product directly inside the container. Their work features, advantages and disadvantages are given. The analysis of the methods of improving the process of processing organic livestock waste in methane tanks is summarized in a table, which presents the essence of the improvement and the expected effect.
Analysis of methods of improving the process of processing organic animal waste in methane tanks
Keywords: біогаз; довкілля; добрива; екологія; метан; температура; теплообмінника; зброджування; biogas; environment; fertilizers; ecology; methane; temperature; heat exchanger; fermentation